Characterization, Comparative Assessment and Antibacterial Potential of Copper(II) Soya Complexes against Staphylococcus Aureus - Dr. Vandana Sukhadia (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
Copper(II) soap complexes have been proven their activity against bacteria very effectively. Herein, the influence of biophysical and biomechanical parameters on the activity of Copper(II) soya thiourea complex was evaluated. To this aim, liquid as well as solid growth media were developed by Kirby-Bauer disc diffusion method. The antibacterial activity of Copper(II) soya thiourea complex against the Gram-positive bacterium Staphylococcus aureus was assessed in various concentration of Copper(II) Soya complexes. Copper (II) Soya complexes also resist bacterial growth at higher concentration. This review provides a board overview of Staphylococcus aureus with an emphasis on the Copper(II) soya thiourea complex
Keywords: Copper (II) Soya Complexes; Photocatalytic Degradation; Staphylococcus Aureus; Antibacterial Activity; Inhibition Zone; Kirby-Bauer Disc Diffusion Method